KARAKTERISASI BERAS ARTIFISIAL SAGU PAPUA DENGAN PENAMBAHAN GELATIN TULANG IKAN TUNA - Tina Fransiskha Carolyn Panjaitan (Faculty of Science and Technology University Ibrahimy, 2017)
Artificial rice sago Papua is one alternative to reduce dependence on rice. The existence of a significant difference in the chemical composition of sago Papua is a high amylose and low amylopectin contentto cause the texture of the rice produced is not good, that is necessary for a binder to improve the texture of artificial rice sago Papua. Binding agent (binder) used is gelatin originating from bones of tuna. Characterization of Papua sago artificial riceconducted to determine the texture (hardness) and the moisture content of artificial rice sago Papua. The purpose of this study was to determine the level of hardness (texture) and the moisture content of artificial ricesago Papua after adding gelatin from the bones of tuna. Characterization process begins with the manufacture of artificial rice followed by a hardness test (texture) and the moisture content of artificialrice sago Papua. The results showed a hardness value (texture) artificial rice sagoPapuais a low of 172.6075 N and high of 266.7990 N. While the moisture content of artificialrice obtained ranged from 9.62 to 9.98%.